Caracterização das Necessidades Educacionais Especiais (NEE) no ensino fundamental II dos colégios estaduais de Marechal Cândido Rondon e o ensino e aprendizagem da Geografia - Rambo , Elisa Bernadete (2022)
This research characterized the teaching and learning of students with Special Educational Needs (SEN) in the discipline of Geography. The number of students with Special Educational Needs in regular education classrooms is expressive and knowledge about this reality is important for the school routine and for the professional practice by teachers. The main objective is to investigate which Special Educational Needs are present in Elementary School II of state schools in Marechal Cândido Rondon and to verify in which years/grades geography teachers find it more difficult to work with geographic content. The methodology consisted of adopting a qualitative-quantitative approach. The quantitative in the conception of empirical investigation, with the objective of checking, recording activities and data, analyzing and evaluating them. The qualitative approach referring to the use of documentary research devices for data collection. The main results found with the development of the research were the increase in the number of students with Special Educational Needs in the regular schools of Marechal Cândido Rondon as well as the increase in the diversity of special needs and that the greatest difficulty of these students appears in the sixth year, in the contents cartographic.